2022
DOI: 10.3389/fphar.2022.937484
|View full text |Cite
|
Sign up to set email alerts
|

Pien-Tze-Huang alleviates CCl4-induced liver fibrosis through the inhibition of HSC autophagy and the TGF-β1/Smad2 pathway

Abstract: Ethnopharmacological relevance: Pien-Tze-Huang (PZH)-a traditional Chinese medicine (TCM) compound-has been employed to treat various liver inflammation and tumors for over 10 decades. Interestingly, most of the pharmacological effects had been validated and explored toward liver ailment along with pro-inflammatory conditions and cancer at the cellular and molecular level to date.Aim of the study: The present study aimed to investigate the therapeutic effect of PZH on autophagy and TGF-β1 signaling pathways in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 60 publications
0
12
0
1
Order By: Relevance
“…Numerous studies have shown that MMPs exhibit low activity under normal conditions and increased activity during inflammation or repair ( Santos et al, 2014 ). In CCl 4 -induced liver fibrosis, mRNA expression of MMP2 and MMP9 in the liver is elevated significantly ( Zhang et al, 2022 ). Additionally, MMP7 mRNA expression is markedly upregulated in kidney tissues of chronic kidney disease patients ( Zheng et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that MMPs exhibit low activity under normal conditions and increased activity during inflammation or repair ( Santos et al, 2014 ). In CCl 4 -induced liver fibrosis, mRNA expression of MMP2 and MMP9 in the liver is elevated significantly ( Zhang et al, 2022 ). Additionally, MMP7 mRNA expression is markedly upregulated in kidney tissues of chronic kidney disease patients ( Zheng et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Z35020242). Its chemical profile has been analyzed through HPLC or UPLC in many studies which have shown similar results that PZH was composited by ginsenoside Rg1, ginsenoside Rg2, ginsenoside Rg3, notoginsenoside R1, ginsenoside Re, ginsenoside Rf, ginsenoside Rh1, ginsenoside Rb1, ginsenoside Rd, glycocholic acid, taurochenodeoxycholic acid, tauroursodeoxycholic acid, taurocholic acid, cholic acid, ursodeoxycholic acid, hyodeoxycholic acid, glycodeoxycholic acid, chenodeoxycholic acid, deoxycholic acid, taurine and muscone ( Qiu et al, 2018 ) ( Zhang et al, 2022 ; Zhang C. et al, 2018 ; Huang et al, 2016 ).…”
Section: Methodsmentioning
confidence: 96%
“…Pien-Tze-Huang (PZH), a well-known Chinese traditional medicine with a long history in China, its formula is a state protected secret which mainly based on Panax notoginseng ( Araliaceae ; Notoginseng radix et rhizoma; Sanqi in Chinese; 85%), Snake bile ( Colubridae ; Bile juice of snake gallbladders; Shedan in Chinese; 7%), Bezoar bovis ( Bovidae ; Dried cattle gallbladder stones; Niuhuang in Chinese; 5%), and Moschus ( Cervidae ; Excretion of Moschus berezovskii Flerov, Moschus sifanicus Przewalski, or Moschus moschiferus Linnaeus; Shexiang in Chinese; 3%) ( Zhang et al, 2022 ), which relieve heat, detoxify, activate blood circulation and remove blood stasis, reducing swelling and pain in the theory of traditional Chinese medicine ( Qiu et al, 2018 ). PZH is usually used for treating inflammatory diseases and tumors ( Qi et al, 2016 ; Chen et al, 2017 ; Li L. et al, 2018 ; Deng et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Так как аутофагия может участвовать в активации СКП, можно сделать вывод, что экзосомы из NK-клеток подавляют активацию CКП именно за счёт переноса miR-223, которая ингибировала аутофагию в результате взаимодействия с ATG7 [88]. Эти данные сходны с результатами, показавшими, что блокирование аутофагии ингибирует развитие фиброза печени [89,90]. Полученные результаты свидетельствуют о перспективности дальнейших исследований по разработке системы доставки экзосом для лечения патологий печени, включая хронические вирусные гепатиты.…”
Section: экзосомы и вирус гепатита вunclassified